2010
DOI: 10.1590/s1516-35982010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Grazing ecology of female lambs on Italian ryegrass plus red clover pasture under different defoliation intensities

Abstract: -The relationship between pasture dynamics and ingestive behavior of female lambs was studied on Italian ryegrass (Lolium multiflorum Lam.) plus red clover (Trifolium pratense L.) mixture under a range of defoliation intensities.Rotational grazing was used and the grazing interval was determined by the thermal sum of 313 degree days. The initial pregrazing canopy height disappearance values were 65 (very high), 58 (high), 47 (medium) and 37% (low). The sward vertical structure was similar among defoliation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This was also demonstrated by Glienke et al (2010) andSeither et al (2012). However, Dumont et al (2011) indicated that other factors such as grazing pressure are even more critical elements affecting changes in botanical composition of swards.…”
Section: Discussionmentioning
confidence: 88%
“…This was also demonstrated by Glienke et al (2010) andSeither et al (2012). However, Dumont et al (2011) indicated that other factors such as grazing pressure are even more critical elements affecting changes in botanical composition of swards.…”
Section: Discussionmentioning
confidence: 88%
“…Temperate forage legumes exhibit promising potential for controlling GIN. Their high protein content, digestibility and acceptance by ruminants makes this group an excellent option for protein supplementation in the diet of grazing sheep (Glienke et al , 2010; Ates et al , 2017; Olubunmi et al , 2019). Moreover, some of these legume forage plants present bioactive properties in controlling GIN, especially due to their content of condensed tannins and flavonoids (Niezen et al , 1995; Oliveira et al , 2011; Wang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%